Residential construction academy - Standiford, Kevin (Thomson Delmar Learning, 2008)
Customer service skills -- Organization of work tasks -- Applied safety rules -- Fasteners, tools, and equipment -- Practical electrical theory -- Electrical facilities maintenance -- Carpentry -- Surface painting -- Plumbing -- Heating, ventilation, and air-conditioning systems -- Appliance repair and replacement -- Trash compactors -- Elevators -- Pest prevention -- Groundskeeping